APLIKASI PENDEKATAN ACTIVE LEARNING TERHADAP KEMAMPUAN PERMAINAN MINI BRIDGE SISWA KELAS IV SD NEGERI 004 RAMBAH SAMO - Debby Indah; Nurtia Nilam Sari (JURNAL PENDIDIKAN ROKANIA, 2018)
The meaning of this research to increase the mini-bridge game ability of class 4 th SD Negeri 004 Rambah Samo. The method used in this research is an quasi experiment that give active learning aplication to rise mini-bridge game ability. The research data shows that, the pre-test mini-bridge game ability is 31,51 percent is lower, and post-test bridge game ability is 56,67 percent is lower. Analysis data indicates that t-count > t-table is 23,32 > 1.645, it meant that theincreasing of active learning aplication against mini-bridge game ability. The increasing of mini-bridge game ability of student is 25,51 percent. Conclusion, the increasing of active learning aplication against mini-bridge game ability of student class 4 th of SD Negeri 004 Rambah Samo.